Pengaruh Ukuran Dewan Komisaris, Profitabilitas Dan Ukuran Perusahaan Terhadap Pengungkapan Islamic Social Reporting (ISR) (Studi Empiris Pada Bank Umum Syariah Di Indonesia Periode 2020 – 2022) - Aulia Aldzani Putri; Khadijah Ath Thahirah (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
This study aims to determine the effect of company size, profitability, and board size on the disclosure of Islamic social reporting. The nature of this research is quantitative. The websites of each bank and the Financial Services Authority (OJK) provide the secondary data used in this study. The results of this study indicate that the size of the board of commissioners partially has a significant effect on the disclosure of Islamic social reporting with the t value of the effect of UDK on ISR disclosure of 2.640> t table value (1.689) with a significance value of 0.012, while profitability with the t value of the effect of profitability on ISR disclosure of 1.220 < t table value (1.689) with a significance value of 0.231 has no effect on the disclosure of Islamic social reporting. As well as company size with the t value of the effect of profitability on ISR disclosure of 1.570 < t table value (1.689) with a significance value of 0.125 has no effect on the disclosure of Islamic social reporting.